The Role of Environmental, Social, and Governance (ESG) and Strategic Efficiency in Enhancing Financial Performance: Evidence from the Food and Beverage Industry in Indonesia - Belinda Mora Siagian; Silvia Tri Handayani; Ratu Aisyah Ratih Primaputri (TECHNOBIZ : International Journal of Business, 2026)
This study examines the role of Environmental, Social, and Governance (ESG) and strategic efficiency in influencing financial performance within Indonesia’s food and beverage industry. The research addresses whether sustainability practices and asset utilization contribute to profitability in the short term. Using a quantitative explanatory approach, the study analyzes 50 firm-year observations from 25 listed companies during the 2023–2024 period. Financial performance is proxied by Return on Assets (ROA), while ESG scores represent sustainability commitment and asset turnover reflects strategic efficiency. Multiple linear regression is employed to test the proposed model. The results indicate that ESG demonstrates a positive relationship with ROA at the 10% significance level, suggesting that sustainability practices begin to contribute to corporate profitability. However, asset turnover and firm size do not show significant effects on financial performance. These findings imply that the impact of sustainability on profitability tends to be gradual and requires consistent strategic integration.